Environmental Management Tools and Forest in Perú: An Overview Regarding COP20 - Sabogal, Ana (Pontificia Universidad Católica del Perú. Centro de Investigación en Geografía Aplicada, 2014)
The environmental instruments to environmental measuring will be analyzed and questioned. An absence of biological instruments will be indicated and the controversial discussion between the economy and biology is also approached. The economy as dominant science has developed instruments that will be accepted as universal languages. On the other hand the biological factors and the environmental services will be transformed in money, which may be a danger for the environmental preservation. The second part of the article is focused on the instruments developed for measuring the worth of forest.